Prevalence and distribution of human papillomavirus genotypes in women with abnormal cervical cytology in Ethiopia: a systematic review and meta-analysis - Kebede, Solomon Demis; Zeleke, Shegaw; Kassaw, Amare; Munye Aytenew, Tigabu; Kefale, Demewoz; Asferie, Worku Necho (Frontiers in Oncology, 2024)
BackgroundCervical cancer is the 4th most common cancer in women globally. Determining the prevalence of the high-risk human papillomavirus (HR-HPV) and low-risk (LR-HPV) genotypes and the distribution in abnormal cervical cytology will be essential in a future population-based cervical cancer prevention program.MethodPrimary studies with women with abnormal cervical cytology were systematically searched for in Medline, CINHAL, Google Scholar, African Journal Online, and the University of Antwerp repository from 19-30 May 2023. A weighted inverse-variance random effects model was used. Variations across the studies were checked using a forest plot, I2 statistics, and Egger’s test. Group analysis was performed for evidence of heterogeneity.ResultsThe pooled prevalence of human papillomavirus (HPV) genotypes with abnormal cervical cytology of a precancerous cervical lesion was 38.74% (95% CI: 27.56-49.93). The leading pooled prevalence estimates by subgroup analysis were 18% (95% CI: 13-26), 14% (95% CI: 111-16), and 66% (51-79) for women with retroviral infection (RVI), DNA genotyping with amplification, and central parts of Ethiopia respectively. There were 25 HPV variants identified by genotyping techniques with the five most prevalent HPV genotypes being HPV-16 and HPV-18 coexisting at 54%; HPV-16 alone at 29%; HPV-51 at 16%; HPV-52 at 13%; and HPV-31 and HPV-33 each contributing approximately 12%.ConclusionThe pooled prevalence of HPV genotypes was higher than in other countries. HPV-51, HPV-52, HPV-31, and HPV-33 are the most prevalent genotypes. Hence, the nonavalent vaccine type would be the one that includes all the most prevalent HPV genotypes, but HPV-51in Ethiopia. Additional data on similar DNA test techniques for comparisons with precancerous lesions and invasive cancer are needed. Cervical cancer prevention and control programs in Ethiopia should be aligned with the most prevalent genotypes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023428955.